Digest of Documents - Harris, J (Paul Holberton Publishing, 2007)
Any attempt to reconstruct the life of André Beauneveu is reliant on a series of documents largely discovered in the course of nineteenth-century archival research and published in many different contexts over the past hundred and fifty years. This material is collected here in date order so as to make possible a full overview of Beauneveu’s career.